O autoritarismo no ponto de vista: desvendando discursos dissonantes em ecossistemas digitais - Fagundes, Isabella Gaboardi (2023)
Authoritarian movements or policies have been and continue to be a focal point of discussions, especially when prominent public figures are involved. With the rise of the power of digital social networks, particularly their widespread use as a means of mobilizing large groups, the exploitation of the imagery of sayings has also become a form of political control and/or government maintenance. It is in this context that this study proposes to analyze the construction and representation of authoritarian discourses as mobilizers of viewpoints in Twitter publications (now is called X). To this end, the research uses as a corpus tweets from the then president of Brazil, Jair Messias Bolsonaro, on one of his social networks, as well as web news from media outlets that used them as targets of criticism in certain statements by the former president that were close to disinformation or incompleteness due to certain controversies involving his comments. Regarding the issue, the premise is that the argumentation presented in these publications/discourses relies on biased enunciative strategies, hence the clash of opinions and the (de)construction of these themes in web news. The theoretical anchoring of the study is based on Rabatel’s (2015; 2018) notion of viewpoint/enunciative responsibility and is also discussed by Cortez (2013; 2018). Within these limits, the research also relies on, relating the same theme to what has been discussed by textual linguistics, especially by the textual/discursive approach of Adam (2011; 2019; 2020) and Cavalcante (2019; 2022; 2022a). From this perspective, we problematize the type of focalization of these two media as their discursive language practices/strategies. Furthermore, we intend to carry out a rescue of the argumentation in the considerations and analyses on the topic, updating it through its use in the environment and space of Web digital technologies, following Paveau (2013; 2020; 2021) mobilizing issues about authoritarianism, according to Silva (2021) and Moreira and Romão (2015), in the field of language, when these discourses permeate disinformation, which emerged from the infodemic, based on Hissa (2021) and Han (2018). Finally, the analyses indicated a certain tendency, in the media, towards axiologization as a way of disqualifying viewpoints and/or arguments of the propositions made, whether through superficial arguments or the attribution of discourse to others with diversion from the subject or even as a method or strategy for changing focus and maintaining biased viewpoints.